2021
DOI: 10.3390/en14133740
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of PV and CSP Systems to Supply Power in the Zimbabwe Mining Sector

Abstract: The drought that occurred in Zimbabwe in 2020 affected the country’s main hydro-power station causing the electricity supply to be less secure and reliable. This challenge resulted in load-shedding, which is not desirable to mining companies that require constant and reliable power for their operations. In that regard, a techno-economic analysis was carried out to assess the potential of integrating concentrated solar power (+thermal storage) and photovoltaics (+battery storage) to supply power at a typical mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The analysis revealed that the cost of producing 214.4 GWh/year of energy at an investment cost of GBP 0.68/Wp was GBP 0.04/kWh, excluding operation and maintenance (O&M) costs. This FPV LCOE is competitive, with a value of GBP 0.0342/kWh and GBP 0.0335/kWh, obtained by Maronga et al [54] and RES4Africa [130], respectively, for ground-mounted PV. Homerpro gave a more conservative annual yield of 175 GWh at an LCOE of GBP 0.067/kWh (including O&M); however, this was without factoring in the water albedo and heat loss factor of the PV module's floating island.…”
Section: Figure 15 Figure Showing Fpv Energy and Efficiency Vs Time (Months)mentioning
confidence: 55%
See 1 more Smart Citation
“…The analysis revealed that the cost of producing 214.4 GWh/year of energy at an investment cost of GBP 0.68/Wp was GBP 0.04/kWh, excluding operation and maintenance (O&M) costs. This FPV LCOE is competitive, with a value of GBP 0.0342/kWh and GBP 0.0335/kWh, obtained by Maronga et al [54] and RES4Africa [130], respectively, for ground-mounted PV. Homerpro gave a more conservative annual yield of 175 GWh at an LCOE of GBP 0.067/kWh (including O&M); however, this was without factoring in the water albedo and heat loss factor of the PV module's floating island.…”
Section: Figure 15 Figure Showing Fpv Energy and Efficiency Vs Time (Months)mentioning
confidence: 55%
“…Typical hybrid energy systems include hydro-PV [47,48], hydro-wind-thermal [49], hydro-wind [50,51] and hydro-wind-PV systems [52,53]. A recent study by Maronga et al [54] evaluated the optimal mix of PV, concentrated solar power (CSP) and storage, for a mining context in Zimbabwe. Previous research [55] found a mix of hydro and photovoltaics to be broadly used in many countries, owing to the vast spread of solar PV as a principal renewable energy source globally, and the swift regulation response of hydropower.…”
Section: Role Of Renewable-energy Hybrid Systems In Energy Transition (Climate Mitigation and Dispatch)mentioning
confidence: 99%
“…Maronga et al [ 12 ] evaluated PV and CSP systems to supply power for the mining sector in Zimbabwe and concluded that PV systems with battery storage offered preferred performance, while CSP with TES showed great potential for more extensive facilities.…”
Section: Concentrated Solar Power (Csp) Technologymentioning
confidence: 99%
“…Rashayi & Chikuni [ 11 ], in a study to analyze the potential of grid-connected PV in Zimbabwe, also considered irradiance as the only determining factor, among other technical factors, to validate the adoption via a LCOE value. In Zimbabwe’s mining industry, Maronga et al’s [ 12 ] evaluation of PV and CSP systems for power supply concluded that PV systems with battery storage offered the best performance, while CSP with TES offered tremendous potential for massive operations. A techno-economic analysis of a 32 MW CSP facility revealed the possibility for extensive CSP operations from Maronga et al [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation